INCREASED ACCESS MEANS DECREASED FORMALITY IN MEDIATION - Schmitt, Nicholas; Adler, Samantha (Lex Electronica, 2023)
One of the greatest advantages of the “digital turn” in mediation, touted by many, is the increased access it can provide to users of mediation. That access could include a person with a disability who need not travel to places that are inconvenient or inaccessible or a busy single parent who can now mediate from their homes. There is no question that digital mediation can allow more people to participate. A disclaimer: this paper does not discuss the many users who might not have access to consistent or high-quality internet access or a device that allows them to access the internet. Even where users have such access, there are some negative side effects to the “digital turn” in mediation and of this increased access; a main one is an associated decrease in formality—at least in non-commercial settings. Decreased formality can lead to decreased engagement in the process, an increase in inflammatory language, an increase in in-group vs. out-group conflicts within the session, acceptance of less fair outcomes by the side with less power, and a greater likelihood that parties will end the process with little or no notice. Professor Delgado was one of the first writers to note that mediation provides a less formal, and therefore potentially less fair process, particularly in divorce mediation and arbitration. Taking mediation online has increased those dangers, some, including Professor Ebner, have written on the potential dangers of the digital mediation process.This paper will explore those dangers and some possible means to attenuate them in the digital world. Some of those means include ways to increase trust, build rapport, and minimize misunderstandings and dishonesty, to ensure that increased access does not become a decrease in the quality of mediation or lead to less fair outcomes for users of mediation in the digital turn.